Identifikasi Karakteristik Permukiman Masyarakat Berpenghasilan Rendah di Area Barat Terminal Pesiapan, Tabanan, Bali - I Made Odde Arca Winata; I Nyoman Ryu Arca Wiguna; I Gede Damarutha Adrian Nugraha; Made Suryanatha Prabawa; Wiwik Widyo Widjajanti (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2021)
Tabanan is one area that has the potential for very rapid development, with problems that arise along with developments in the region. If the population increases, if it is not followed by the development of settlements, it will lead to the emergence of settlements that are not suitable for habitation, with dense capacities, and will have an impact on the condition of the surrounding environment which becomes unfavorable, thus creating slum settlements in the area. The purpose of using the Tabanan area as an analysis of slum settlements is that this area has considerable potential for unorganized development, considering the increasing number of residents who are not accompanied by settlement development. In this settlement there are several facilities available, but with their ineffective use, this settlement becomes a slum. The problem of the economic crisis is very familiar among the people caused by the availability of job opportunities with demands that must be met. The majority of residents from these settlements have low incomes which causes residents to have makeshift houses by utilizing available materials or goods.